2014
DOI: 10.1002/bjs.9394
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of enhanced recovery programmes in surgical patients

Abstract: ERPs are effective in reducing length of hospital stay and overall complication rates across surgical specialties. It was not possible to identify individual components that improved outcome. Qualitative synthesis may be more appropriate to investigate the determinants of success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
262
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(276 citation statements)
references
References 62 publications
5
262
1
8
Order By: Relevance
“…37,38 Most ERAS programs also report faster return of bowel function after colorectal surgery by about one day. 38 Nevertheless, it proves more difficult to synthesize other outcomes between studies because multiple definitions and instruments are being used.…”
Section: Are There Recovery-specific Qol Instruments?mentioning
confidence: 99%
“…37,38 Most ERAS programs also report faster return of bowel function after colorectal surgery by about one day. 38 Nevertheless, it proves more difficult to synthesize other outcomes between studies because multiple definitions and instruments are being used.…”
Section: Are There Recovery-specific Qol Instruments?mentioning
confidence: 99%
“…The ERP is a comprehensive perioperative CRS care pathway that has been shown to reduce postoperative morbidity and length of hospitalization. [9][10][11][12][13][14][15][16][17] Similarly, the SSIB is a perioperative care program that systematically provides evidence-supported measures for surgical wound infection prevention and has been shown to reduce the rate of postoperative wound infection. [18][19][20][21][22] Although both the ERP and SSIB have individually been shown to improve outcomes after CRS, the effect of their combined presence has not, to our knowledge, previously been reported in the literature.…”
mentioning
confidence: 99%
“…ERPs were also associated with a 30 % reduction in complications at 30 days, with no increased risk of major complications or death. The effect was similar across different disciplines and for laparoscopic versus open colorectal surgery [19]. A separate meta-analysis of 13 randomized trials in colorectal surgery also found a shorter hospital stay by about 2 days, without increased readmissions.…”
Section: Outcomes Of the Erp Approachmentioning
confidence: 53%
“…It is not simply a set of standard orders; in addition it should address patient preparation, intraoperative management, and audit. This approach helps introduce evidence into practice and results in less morbidity, less need to remain in hospital, less variability between practitioners, and lower resource use [16][17][18][19].…”
Section: Liane S Feldmanmentioning
confidence: 97%
See 1 more Smart Citation